Interaction of Adiponectin Genotypes and Insulin Resistance on the Occurrence of Taiwanese Metabolic Syndrome. (3rd May 2021) - Chen, Chun-Chieh; Wei, Yu-Hsiang; Huang, Chia-Chen; Hung, Shin-Hui; Wang, Zeng-Wei; Wong, Ruey-Hong
Abstract : Backgrounds. Adiponectin (apM1) may affect insulin sensitivity, and tumor necrosis factor (TNF- α ) can inhibit the binding of insulin and insulin receptors. However, whether apM1 and TNF-α genes influence the development of metabolic syndrome (MetS) preceded by insulin resistance is unclear. The current study examines the interactions between the apM1 +45 genotypes, TNF-α -308 genotypes, and insulin resistance on the occurrence of MetS. Methods. A total of 329 community residents were recruited, and their personal characteristics were collected. Waist circumference and biochemical markers were examined for determining MetS. Genotypes were identified by the polymerase chain reaction. Results. After adjusting for the confounding effects, compared to apM1 +45 GG and GT genotypes carriers with HOMR-IR less than 2.0, those carriers with HOMA-IR greater than 2.0 had an increased MetS risk (OR = 4.35, 95% CI 2.14-8.85). Further, apM1 +45 TT carriers with HOMA-IR greater than 2.0 experienced a higher MetS risk (OR = 5.91, 95% CI 2.78-12.54). A significant interaction of the apM1 +45 genotype and insulin resistance on the MetS development was observed (P = 0.04 ). Conclusion. Our data suggested that apM1 +45 genotypes might modify the effect of insulin resistance on the development of Taiwanese MetS.